PENGARUH KESIMPULAN KERAPATAN ADAT NAGARI (KAN) TERHADAP PUTUSAN HAKIM DALAM PERKARA PERDATA DI PENGADILAN NEGERI PADANG - Mardius , (Fakultas Hukum Universitas Tamansiswa Padang, 2018)
Civil cases in the District Court are caused by disputes between individuals in the civil service. Those who feel aggrieved by other parties in the relationship can file a lawsuit with the District Court. In order for our lawsuit to be granted by the judge, there is evidence that corroborates our lawsuit. One of these factors is the Conclusion of Traditional Density in Nagari, the letter produced by the Kerapatan Nagari Institute in the area as decisive evidence in the decision of a civil case. Conclusion Indigenous Density of Nagari is one of the most decisive proofs of the Judge's decision that the case object is in the form of matters relating to the High inheritance in Minaingkabau, so that the judge in the District Court made the Conclusion on Indigenous Density of Nagari used as a reference to decide a civil case the object is a high inheritance property as well as of course other evidence.